Cover Image, Volume 138, Issue 34. Issue 34 (2nd June 2021) - Simon, Sanu Mathew; George, Gejo; Chandran, Anoop; Valparambil, Prakashan; M. Shamsudeen, Sajna; Saritha, A. C.; Biju, P. R.; Thomas, Sabu; Joseph, Cyriac; Vishwambharan, Unnikrishnan N.
Abstract : Surface engineered self‐cleaning property has captured wide attention in scientific, as well as industrial arenas recently. Better protection from environmental pollutants and dirt that might adversely affect its performance is a key requirement for coatings that offer self‐cleaning. The cover designed by Unnikrishnan N V and colleagues shows the development of self‐cleaning microsphere coatings with a prolonged lifetime using an sol‐gel assisted electro‐spraying approach. In addition, high quality selfcleaning surfaces are generated by altering the type of polymers used. And modulating surfaces by addition of tri‐block co‐polymer is found to provide swapping of superhydrophobic nature to superhydrophilic nature. Better antibacterial and photocatalytic properties are shown by the samples. DOI: 10.1002/app.50880